KOHERENSI DALAM PIDATO STEVE JOBS - ARINA, ARTEN RISKI (JURNAL ELEKTRONIK FAKULTAS SASTRA UNIVERSITAS SAM RATULANGI, 2016)
ABSTRACT This study entitled ‘Coherence in Steve Jobs Speech’ Coherence is a study about relation of meaning between sentence in the text, and coherence is one of the seven norms in discourse analysis. This study is attempt to identify, classify, and analyze the relation of meaning of coherence contained in the speech. The data collected, the writer reads the speech of Steve Jobs for several times deep understanding. The writer used the theory of Alba-Juez and supported the theory by Van Dijk the theory consist of coherence, mark coherence and unmark coherence. The result of this research shows that in marked coherence there are 139 pronouns, this marked coherence are as follow: 83 Addition, 14 Contrast, 4 Causality, 7 Condition, 11 Conclusion, 14 Tempo, 4 Intensity. And there is no unmarked coherence. This speech contains the coherence suggested by Juez (2008). Keywords: discourse analysis, coherence, speech, Steve Jobs